Pigment epithelium derived factor as a novel multi-target treatment for uterine fibroids. Issue 2 (August 2020) - Bar-Joseph, Hadas; Hikri, Elad; Chuderland, Dana; Ben-Ami, Ido; Shalgi, Ruth
Abstract: Research question: Does recombinant pigment epithelium derived factor (PEDF) have potential in treating uterine fibroids? Design: In-vitro models that used human leiomyoma and Eker rat uterine leiomyoma (ELT-3) cell lines. The ELT-3 cell line was used to examine cellular targets after adding recombinant PEDF to the culture media. Athymic nude female mice were used as an in-vivo model. They were injected with ELT-3 cells to induce ectopic fibroid lesions, then treated with recombinant PEDF. Results: RNA expression of PEDF and its receptors was found in both leiomyoma cell lines, as well as the expression of PEDF receptors. Addition of recombinant PEDF to the culture medium of leiomyoma cell lines activated ERK in a time-dependent manner, induced down-regulation of vascular endothelial growth factor mRNA and protein, as well as the mRNAs of oestrogen receptors alpha and beta and inhibited cellular proliferation. Treatment of mice-bearing fibroids with recombinant PEDF reduced fibroid growth rate and resulted in smaller tumours. Conclusions: This study suggests that recombinant PEDF is a putative novel potent physiological treatment for uterine fibroids. It targets several cornerstones of fibroid pathobiology in parallel, including vascular endothelial growth factor and oestrogen receptors, which are needed for vascularization, and restricts fibroid growth and final size in an animal model. Graphical abstract: Image, graphical abstract